Analysis of Stigma and Myths on Medication Adherence in Pulmonary Tuberculosis Patients - Vivop Marti Lengga; Nur Intan Hayati Husnul Khotimah; Silvi Nindiani Putri; Raden Siti Jundiah; Haerul Imam; Sri Wulan Megawati; Ade Iwan Mutiudin; Sumbara Sumbara (Indonesian Journal of Global Health Research, 2026)
Pulmonary Tuberculosis (TB) remains a global and national health problem, including in Indonesia as the country with the second-highest TB burden in the world. TB control efforts are strongly influenced by patient adherence to long-term treatment. Various social and psychological factors, including stigma and myths about TB, have the potential to affect patient adherence, but empirical evidence at the community level is still limited. This research aims to analyze the relationship between stigma and myths and medication adherence in pulmonary tuberculosis patients. The research design used a quantitative correlational approach. A sample of 40 respondents was obtained through a total sampling technique. The instruments used included the ISTB-12 to measure stigma and the M-TBQ for myths, that have undergone content validity testing and were declared valid by two experts and construct validity test yielded a Cronbach's alpha > 0.6 (reliable). The third instrument measuring medication adherence was the MARS-5, which has been validated and proven reliable. Correlation analysis was performed using the Theta (θ) test because the data was not normally distributed with an ordinal-numeric scale. The Theta test results showed a relationship between stigma and medication adherence (θ = 0.219; low correlation), while myths were not related to adherence (θ = 0.038). Stigma is proven to be associated with medication adherence, although with a low strength of relationship, while myths do not affect adherence in pulmonary TB patients.